Aesthetics as a Normative Science. (3rd October 2014) - Graham, Gordon
<x content-type="archive" xml:space="preserve">Abstract</x> It is well known that we owe the term 'aesthetics' in its philosophical sense to the 18th century German philosopher Alexander Baumgarten. The eighteenth century's interest in aesthetics, however, pre-dated the invention of the term. In 1725, Francis Hutcheson published an Inquiry into the Original of Our Idea of Beauty and Virtue. This may be said to be the first sustained and significant work in philosophical aesthetics as we now know it. Hutcheson's volume preceded Baumgarten's by 10 years, and within Scotland it inaugurated a series of philosophical writings on taste and beauty that continued for almost a century. Contributors included major philosophical figures like David Hume, Thomas Reid and Adam Smith, as well as influential figures less well known today such as Alexander Gerard, George Turnbull and Lord Kames.